Off-target capture data, endosymbiont genes and morphology reveal a relict lineage that is sister to all other singing cicadas - Simon, Chris (2019)
Phylogenetic asymmetry is common throughout the tree of life and results from contrasting patterns of speciation and extinction in the paired descendant lineages of ancestral nodes. On the depauperate side of a node, we find extant ´relict´ taxa that sit atop long, unbranched lineages. Here, we show that a tiny, pale green, inconspicuous and poorly known cicada in the genus Derotettix, endemic to degraded salt-plain habitats in arid regions of central Argentina, is a relict lineage that is sister to all other modern cicadas. Nuclear and mitochondrial phylogenies of cicadas inferred from probe-based genomic hybrid capture data of both target and non-target loci and a morphological cladogram support this hypothesis. We strengthen this conclusion with genomic data from one of the cicada nutritional bacterial endosymbionts, Sulcia, an ancient and obligate endosymbiont of the larger plant-sucking bugs (Auchenorrhyncha) and an important source of maternally inherited phylogenetic data. We establish Derotettiginae subfam. nov. as a new, monogeneric, fifth cicada subfamily, and compile existing and new data on the distribution, ecology and diet of Derotettix. Our consideration of the palaeoenvironmental literature and host-plant phylogenetics allows us to predict what might have led to the relict status of Derotettix over 100 Myr of habitat change in South America.